2013
DOI: 10.1109/joe.2012.2224536
|View full text |Cite
|
Sign up to set email alerts
|

NEMO-SN1 Abyssal Cabled Observatory in the Western Ionian Sea

Abstract: The NEutrinoMediterranean Observatory-Submarine Network 1 (NEMO-SN1) seafloor observatory is located in the central Mediterranean Sea, Western Ionian Sea, off Eastern Sicily (Southern Italy) at 2100-m water depth, 25 km from the harbor of the city of Catania. It is a prototype of a cabled deep-sea multiparameter observatory and the first one operating with real-time data transmission in Europe since 2005. NEMO-SN1 is also the first-established node of the European Multidisciplinary Seafloor Observatory (EMSO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 19 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…Technological progress has greatly improved our capability in deploying and recovering the observatories and the seafloor sensors safely. Using an electro-optical cable connecting the seafloor observatory to an on-land station, it is possible to retrieve data in real time, and to supply power to the observatory (e.g., Favali et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Technological progress has greatly improved our capability in deploying and recovering the observatories and the seafloor sensors safely. Using an electro-optical cable connecting the seafloor observatory to an on-land station, it is possible to retrieve data in real time, and to supply power to the observatory (e.g., Favali et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The marine industry was largely responsible for technical advances and science propagation, which justifies the significant number of articles that have a technical and economic perspective. More recently, there is a trend towards studies with social perspectives and networks of seafloor observatories for continuous geohazards monitoring [35,54,[217][218][219]. Therefore, direct monitoring represents a complementary manner, alongside conventional techniques in which environmental conditions call for deployment and provide enhanced confidence regarding geohazard assessments [139].…”
Section: Discussionmentioning
confidence: 99%
“…Marine geohazard surveys in the Mediterranean Sea were more frequent and this sea was the most studied, see Figures 5 and 7. For example, the publications by Italian authors revealed the impact of scientific efforts to recognize the geohazards along the Italian continental margin [34][35][36][37][38][39][40][41], one of the most seismically active regions in the central Mediterranean and the longest record of historical earthquakes in the world [41]. The data indicated without doubt the growth, evolution, and territorial expansion related to the research on marine geohazards.…”
Section: Time and Spacementioning
confidence: 99%
“…Static hydrophone arrays, using underwater buoys, provide stable recordings and observations of foraging [1]- [3] but can only monitor a fixed location, making it difficult to track animals over longer distances. A bottommounted array with small aperture (2m) and high sampling rate has been deployed for 3D localization of multiple whales [4], [5]. More flexibility can be achieved by mounting hydrophones on a vessel.…”
Section: Introductionmentioning
confidence: 99%